Comparison of Total Phenolic Content, Antioxidant Activity and Trans-Resveratrol Content of Fresh Red Grapes and Raisin Ethanolic Extracts - Komutiban, Dr. Orapin; Katkaew, Ailada; Jaisamut, Janissata; Jaisamut, Janissata (Journal of Food Health and Bioenvironmental Science, 2018)
The aim of this research was to determine the total phenolic content, antioxidant activity, and trans-resveratrol content of red grape ethanolic extracts obtained from 2 varieties from Thailand and 4 international varieties and raisin ethanolic extracts. All grape extracts showed total phenolic value range of 165.90 ± 4.49 to 272.21 ± 1.96 mg GAE/g extract. For antioxidant activities determined by DPPH and TEAC methods, all the extracts showed significant antioxidant activities at p < 0.05. The trans-resveratrol content was found at the highest value of Cardinal grape (42.47 ± 0.41 μg/g extract). Heat treatments to Cardinal grape at temperatures of 60 °C and 70 °C for 24, 48 and 72 hours resulted in a decrease of total phenolic content, antioxidant activity and trans-resveratrol content compared with unheated grape.